A Fed-Batch Synthetic Strategy for a Three-Step Enzymatic Synthesis of Poly-epsilon-caprolactone - Scherkus, Christian; Schmidt, Sandy; Bornscheuer, Uwe T.; Gröger, Harald; Kara, Selin; Liese, Andreas (ChemCatChem, 2016)
Scherkus C, Schmidt S, Bornscheuer UT, Gröger H, Kara S, Liese A. A Fed-Batch Synthetic Strategy for a Three-Step Enzymatic Synthesis of Poly-epsilon-caprolactone. CHEMCATCHEM . 2016;8(22):3446-3452. A three-step enzymatic reaction sequence for the synthesis of poly-epsilon-caprolactone (PCL) was designed running in a fed-batch operation. The first part of the cascade consisted of two oxidation steps starting with alcohol dehydrogenase catalyzed oxidation from cyclohexanol to cyclohexanone and further oxidation to epsilon-caprolactone (ECL) by means of a Baeyer-Villiger monooxygenase. As a third step, lipase-catalyzed hydrolysis of the lactone to 6-hydroxyhexanoic acid (6-HHA) was designed. With this biocatalytic multistep process reported herein, severe substrate surplus and product inhibition could be circumvented by the fed-batch operation by adding the cyclohexanol substrate and by in situ product removal of ECL by hydrolysis, respectively. Up to 283 mm product concentration of 6-HHA was reached in the fed-batch operated process without loss in productivity within 20 h. After extraction and subsequent polymerization catalyzed by Candida antarctica lipase B, analysis of the unfractionated polymer revealed a bimodal distribution of the polymer population, which reached a mass average molar mass (M-w) value of approximately 63 000 g mol(-1) and a dispersity (M-w/M-n) of 1.1 for the higher molecular weight population, which thus revealed an alternative route to the conventional synthesis of PCL.